DEVELOPING OPEN-ENDED QUESTIONS FOR SURFACE AREA AND VOLUME OF BEAM - Henry Kurniawan; Ratu Ilma Indra Putri; Yusuf Hartono (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2018)
The purpose of this research was to show open-ended questions about surface area and beam volume which valid and practice, have potential effect. This research is research development which consists of two main phases: preliminary phase (preparation phase and problem design) and formative evaluation phase (evaluation and revision phases). The objective of the study is the students of VIII.2 class of Junior High School 55 Palembang. The result of the study got 9 questions open-ended of surface area and beam volume materials which valid and practical. In addition, there was the potential effect of students' mathematical ability on the open-ended questions that have been given. The result of open-ended problem in the concept potential effect was 77,53%, reasoning ability was 59,79%, the communication ability was 57,02%, and problem solving ability was 67,01 %.DOI: http://dx.doi.org/10.22342/jme.9.1.4640.157-168